Susceptibility of Aedes albopictus from dengue outbreak areas to temephos and Bacillus thuringiensis subsp. israelensis - Ahmad Mohiddin; Asmalia Md Lasim; Wan Fatma Zuharah (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To monitor the current duration of the application rates in vector programme and the level of Aedes albopictus larvae susceptibility from three selected areas in northeast district of Penang on two selected larvicides, temephos and Bacillus thuringiensis subsp. israelensis (Bti) which are commonly used by Penang Health Department for vector control. Methods: The mosquito larvae were tested against two types of larvicides: (1) temephos (Abate®) with diagnostic dosage (0.012 mg/L) and operational dosage (1 mg/L) and (2) Bacillus thuringiensis subsp. israelensis (VectoBac® WG) with operational dosage ranging from 6000 international toxic units per L to 24000 international toxic unit per L. A total of 20 late third and early forth instar larvae were selected and transferred into paper cup sized 300 mL using wide-mouthed pipette. The larvae were distributed into each 300 mL paper cup containing 50 mL of aged tap water. The experiment was replicated five times for each concentration tested. Each test was repeated three times. The mortality was recorded after 24 h of exposure and recorded lethal time was based on 2 h for temephos and 6 h for Bti. The control consisted of ethanol for temephos and only seasoned water for Bti. Results: The result showed that Aedes albopictus from Flat Hamna, Kampung Sungai Gelugor and Kampung Tanjung Tokong were still susceptible to Bti and temephos. However, higher lethal time and resistance ratio were detected in strain from Flat Hamna which was a known dengue hot spot area in northeast of Penang. Conclusions: The application of temephos and Bti in vector control activity in these selected localities is still relevant in the control of Aedes larvae populations.